Heat transfer characteristics of plate fin heat sink with longitudinal vortex generators - Santhanakrishnan, Mani Sekaran; Tilford, Timothy; Bailey, Christopher (Emerald, 2023)
Purpose This study aims to provide an insight into the relationship between design parameters and thermal performance of plate fin heat sinks (PFHSs) incorporating longitudinal vortex generators (VGs) inside a PFHS channel. Design/methodology/approach A computational fluid dynamics model of a delta winglet pair VG mounted inside a PFHS geometry is detailed, and the model is validated by comparison with experimental data. The validated model is used to perform a virtual design of experiments study of the heat sink with bottom plate and vertical plate mounted VGs. Data from this study is used to regress a response surface enabling the influence of each of the assessed design variables on thermal performance and flow resistance to be determined. Findings The results of this study show that the thermal hydraulic performances of a PFHS with bottom plate mounted VG and vertical plate fin mounted VG are, respectively, 1.12 and 1.17 times higher than the baseline PFHS. Further, the performance variation of the heat sink with VG, relative to delta winglet’s arrangement (common flow up and common flow down), trailing edge gap length and Reynolds number were also evaluated and reported. Originality/value For the first time, performance characteristics of delta winglet VGs mounted inside the PFHS are evaluated against different design variables and a polynomial regression model is developed. The developed regression model and computed results can be used to design high performance PFHSs mounted with delta winglet VGs.
Keywords: computational fluid dynamics; response surface model; vortex generator; heat exchanger; plate fin heat sink